A Comparison on Business Negotiation Styles with Education - Tu, Yu-Te (Information Management and Business Review, 2012)
Training and education is important in negotiation. For a trained negotiator, good results are the consequence of knowing when to follow to his/her instincts and when to employ negotiation theories or use a combination of them. As the economics within Greater China become more internally linked together, it becomes increasingly important to understand the nuances of each culture encompassed by this term. There is very little comparing the negotiation styles of Chinese who live in Taiwan, Hong Kong, and China among themselves. To fill the gap, the present research focuses on negotiations style comparison by education among Chinese in Taiwan, Hong Kong, and China. The population was chosen from public companies listed under the stock markets. Data was collected using an online survey technique. SPSS was used to conduct data analyses, and a variety of statistical measures were used, including descriptive statistics and MANOVA, and coefficient alphas was reported for modified instruments in order to address reliability and validity of the instrument. The results indicated that three dimensions-intuitive, normative, and analytical-had a significant relationship affected by education among the three regions. The researcher suggests that the negotiators still need to be trained in body language, strategies, temper control, international manners, and customs. A better knowledge of negotiation should be helpful in understanding business and in realizing which negotiation styles are most appropriate for a particular country. The appropriate negotiation skills can bring more competitive advantages and benefits.